(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
Information about biology of Anthurus archeri (Berk.) E. Fisch. (Clathraceae, Basidiomycota), an invasive fungus from Australasia, which is widely naturalized in Europe, is given for Ukraine. A. archeri was found in Ukrainian part of Carpathian Mts. in deciduous forests on places rich of organic matter.